Antibodies against TFPI and protein C are associated with a severe thrombotic phenotype in patients with and without antiphospholipid syndrome. Issue 170 (October 2018) - Efthymiou, M.; Arachchillage, D.R.J.; Lane, P.J.; O'Keeffe, A.G.; McDonnell, T.; Cohen, H.; Mackie, I.J.
Abstract: Background: Tissue factor pathway inhibitor (TFPI) antibodies, which have been reported in patients with antiphospholipid syndrome (APS), may impair TFPI activity and contribute to hypercoagulability, but their role in APS and in thrombosis remains undefined. Objective/methods: We assessed the presence and avidity of TFPI IgG antibodies, associations with protein C IgG antibodies and associations with clinical disease severity, in 50 patients with thrombotic APS and 50 thrombotic control patients, on long term anticoagulation with warfarin. Results: Thrombotic APS patients had a significantly higher prevalence of TFPI IgG antibodies (40%; 20/50) compared to thrombotic controls (18%; 9/50). TFPI antibodies were predominantly high avidity in APS (50%, 10/20 of positive patients) and strongly associated with a severe thrombotic phenotype (venous and arterial thromboembolism or recurrent thromboembolic episodes despite therapeutic anticoagulation) (odds ratio (OR): 12.0, 95%CI: 2.2–66.1, p = 0.004), while thrombotic control patients mainly showed low avidity antibodies (78%, 7/9 of positive patients). Coexistence of TFPI and protein C IgG antibodies, regardless of their avidity, was strongly associated with a more severe thrombotic phenotype in APS patients (OR: 20.2, 95%CI: 2.0–47.0, p < 0.0001) and also in thrombotic controls (OR: 75.0, 95%CI 1.2–195, p = 0.02). Conclusions: Coexistent TFPI and protein C IgG antibodies, irrespective of their avidity, may be a useful marker for a severe thrombotic phenotype in thrombotic patients. This suggests a possibly pathophysiological relationship between the two antibodies, predisposing to thrombosis with a possibly more general role in the development of thrombotic complications. Highlights: TFPI and protein C (PC) antibodies (abs) have been reported in APS. We examined prevalence and avidity and associations with severity of clinical phenotype in APS. TFPI abs show high prevalence in APS (40%); and thrombotic controls (18%). Mostly high/intermediate avidity in APS, associated with severe thrombotic phenotype Coexistent with PC abs, regardless of avidity, may be a marker for a severe thrombotic phenotype in thrombotic patients.